ZBP1 senses Brucella abortus DNA triggering type I interferon signaling pathway and unfolded protein response activation - Gomes, Marco Túlio R.; Guimarães, Erika S.; Oliveira, Sergio C. (Frontiers in Immunology, 2025)
The innate immune system promptly detects and responds to invading pathogens, with a key role played by the recognition of bacterial-derived DNA through pattern recognition receptors. The Z-DNA binding protein 1 (ZBP1) functions as a DNA sensor inducing type I interferon (IFN) production, innate immune responses and also inflammatory cell death. ZBP1 interacts with cytosolic DNA via its DNA-binding domains, crucial for its activation. Brucella abortus is the etiologic agent of brucellosis in livestock and humans, leading to significant economic losses and public health impact. Despite other innate immune sensors that recognize B. abortus DNA, including Toll-like receptor 9 and the Stimulator of interferon genes (STING), here we evaluated the ZBP1 participation as a cytosolic receptor sensing Brucella infection. Using macrophages derived from ZBP1 knockout (KO) mice we demonstrated that ZBP1 partially contributes to IFN-β expression upon B. abortus infection or Brucella DNA transfection. The knockdown of STING by siRNA decreased the residual IFN-β signal elicited by B. abortus infection, demonstrating the presence of a redundant cytosolic DNA-sensing mechanism driving type I IFN production. Furthermore, ZBP1 is involved in type I IFN signaling inducing IRF-1 expression. Additionally, ZBP1 also contributes to Unfolded Protein Response (UPR) activation during infection. However, ZBP1 does not influence the production of proinflammatory mediators, inflammasome activation and it is dispensable to control bacterial infection in mice or replication in macrophages. This study highlights the complex interactions of Brucella components with innate immune receptors and identifies ZBP1 as a sensor for B. abortus DNA-induced IFN-β response.